Addressing the food security and conservation challenges: Can be aligned instead of apposed? - Jouzi, Zeynab; Leung, Yu-Fai; Nelson, Stacy (Frontiers in Conservation Science, 2022)
This perspective article provides an overview of the interaction between food security and conservation as two of the most important challenges of our time. To provide a better understanding of the topic, a conceptual framework for the possible pathways of positive and negative impacts of protected areas (PAs) on four dimensions of food security is proposed. Considering the importance of hunting and shifting agriculture in food security and the challenges caused by them in conservation, the cases of hunting and shifting agriculture were explored. Finally, the rights-based approaches in conservation and food security, as a new approach with the potential to protect people and the planet as a synergistic approach is discussed.